SPIRITUALISME DALAM NOVEL THE LAND OF MIST KARYA SIR ARTHUR CONAN DOYLE - Rantung, Risky (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2015)
ABSTRACT This skripsi entitled â€œSpiritualisme dalam Novel The Land of Mist karya Sir Arthur Conan Doyleâ€, is focused on Spiritualism which a system of belief that human can contact the spirit in the afterlife. The aim of this research is to identify, to analyze, and to explain the idea of Spiritualism within the novel. In order to achieve those aims, literature and idea coined by Wellek-Warren is the theory that has been used. The method of this research is descriptive, and the approaches are both intrinsic and extrinsic. The intrinsic approach used in analyzing and interpreting the work, emphasizes on the spiritualism through the plot, character, and settingwhich reflecting Conan Doyleâ€™s belief in spiritualism. The extrinsic approach has been used in analyzing the relationship between the work, Conan Doyleâ€™s life and the spiritualism belief. Moreover, the result of the research shows that the ideology of Spiritualismalso embraced by Sir Arthur Conan Doyle, is heavily contained in his novel The Land of Mist. The corporated ideologies could be found in the novel such as, clairvoyance, clairaudience, ectoplasm, trance, spheres, apports, levitation, materialization, psychometry, and direct voice. Keywords: spiritualism, belief, supernatural, Conan Doyle, ideology